2018
DOI: 10.1039/c8bm00548f
|View full text |Cite
|
Sign up to set email alerts
|

In vivotailor-made protein corona of a prodrug-based nanoassembly fabricated by redox dual-sensitive paclitaxel prodrug for the superselective treatment of breast cancer

Abstract: Prodrug self-nanoassemblies have many advantages for anticancer drug delivery, including high drug loading rate, resistance to recrystallization, and on-demand drug release. However, few studies have focused on their protein corona, which is inevitably formed after entering the blood and determines their subsequent fates in vivo. To actively tune the protein corona of prodrug nanoassemblies, three maleimide-paclitaxel prodrugs were synthesized via different redox-sensitive linkers (ester bond, thioether bond a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…The cytotoxicity of PTX-sol and prodrug NPs toward cancer cell lines (4T1) and normal cell line (NIH/3T3) were evaluated by MTT assays. 25,36 According to previous studies, the group of free anticancer drug always showed a higher cytotoxicity than prodrug nano-formulations due to the delayed drug release and the P-glycoprotein to exocytose of anticancer drugs. 24,30,37 However, compared to PTX-sol group in this study, the prodrug NPs exhibited a considerable cytotoxicity of 4T1 cancer cells ( Fig.…”
Section: Cytotoxicitymentioning
confidence: 98%
See 4 more Smart Citations
“…The cytotoxicity of PTX-sol and prodrug NPs toward cancer cell lines (4T1) and normal cell line (NIH/3T3) were evaluated by MTT assays. 25,36 According to previous studies, the group of free anticancer drug always showed a higher cytotoxicity than prodrug nano-formulations due to the delayed drug release and the P-glycoprotein to exocytose of anticancer drugs. 24,30,37 However, compared to PTX-sol group in this study, the prodrug NPs exhibited a considerable cytotoxicity of 4T1 cancer cells ( Fig.…”
Section: Cytotoxicitymentioning
confidence: 98%
“…In our previous study, the thioether bond in the prodrug-based NPs could be cleaved by ROS for on-demand drug release. 22,25 In this section, the in vitro release of PTX from NPs were studied under different concentration of H 2 O 2 ( Fig. 2c and d), to investigate the efficiency of the thioether bond in this prodrug-based NPs response to ROS.…”
Section: Characterization Of Prodrug Npsmentioning
confidence: 99%
See 3 more Smart Citations